2015
DOI: 10.1126/science.aac7420
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the metazoan Nup62•Nup58•Nup54 nucleoporin complex

Abstract: Nuclear pore complexes (NPCs) conduct nucleocytoplasmic transport and gain transport selectivity through nucleoporin FG domains. Here, we report a structural analysis of the FG Nup62•58•54 complex, which is a crucial component of the transport system. It comprises a ≈13 nanometer-long trimerization interface with an unusual 2W3F coil, a canonical heterotrimeric coiled coil, and a kink that enforces a compact six-helix bundle. Nup54 also contains a ferredoxin-like domain. We further identified a heterotrimeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
130
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(143 citation statements)
references
References 49 publications
12
130
1
Order By: Relevance
“…Similar to the Y-complex, the Nup93 complex forms four eight-membered stacked rings resulting in 32 copies of the complex per NPC. The NPC inner ring represents the link between the pore membrane and the permeability barrier formed by FG-repeat nucleoporins: Nup93 positions the Nup62 complex, which forms a large part of the central transport channel of the NPC Chug et al, 2015). Attached to this generally symmetric NPC structure are the nuclear basket and cytoplasmic filaments, asymmetric extensions that extend into their respective compartments.…”
Section: Npc Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the Y-complex, the Nup93 complex forms four eight-membered stacked rings resulting in 32 copies of the complex per NPC. The NPC inner ring represents the link between the pore membrane and the permeability barrier formed by FG-repeat nucleoporins: Nup93 positions the Nup62 complex, which forms a large part of the central transport channel of the NPC Chug et al, 2015). Attached to this generally symmetric NPC structure are the nuclear basket and cytoplasmic filaments, asymmetric extensions that extend into their respective compartments.…”
Section: Npc Architecturementioning
confidence: 99%
“…Nup53 recruits Nup155 and Nup93, which is in complex with one of the two paralogs Nup188 or Nup205 (Hawryluk-Gara et al, 2005;Theerthagiri et al, 2010;Sachdev et al, 2012;Eisenhardt et al, 2014). Nup93 also recruits, through its N-terminal coiled-coil domain, the Nup62 complex, which consists of the FG-repeatcontaining nucleoporins Nup62, Nup58 and Nup54 Chug et al, 2015), which forms a large part of the hydrophobic meshwork within the central NPC. At the same time, Nup98, another FG-repeat-containing nucleoporin that is also crucial for the exclusion and transport properties of the NPC (Laurell et al, 2011;Hulsmann et al, 2012), is integrated into the structure .…”
Section: Npc Assemblymentioning
confidence: 99%
“…As proof in point, we did not obtain interactions for hsNup160 (162 kDa) and hsNup155 (155 kDa). On the other hand, three well-studied interactions were found in the human and the yeast screens: (i) the Y-complex interaction between hsNup133-Nup107 (7,40,41), (ii) the hsNup54 -Nup62 and scNup57-Nsp1 interactions in the hsNup62/scNsp1-complex (15)(16)(17)42), and (iii) the hsNup93-Nup35 interaction interolog to the scNic96 -Nup53 interaction (37,43). Similar to the hsNup133-Nup107 interaction that complemented the yeast network, additional human Nup interactions were found.…”
Section: Comprehensive High-resolution Y2h Ppi Screening Formentioning
confidence: 99%
“…Crystallographic studies of scaffold Nups have revealed that they are largely composed of ␤-propellers and stacked ␣-helical domain elements (4,5). At least three architectural subcomplexes can be biochemically defined: the heteromeric Y-complex (6 -10), the heteromeric (yeast) Nic96/ (human) hsNup93 complex (11,12) and the trimeric Nsp1/ hsNup62 complexes (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…It remains to be determined whether any change in the diameter of the NPC is force-regulated and whether components of the LINC complex have a role in NPC dilation and constriction. It should be noted that the dilation and/or constriction of the NPC is still a matter of controversy and has been refuted by some experimental studies and observations (Stuwe et al, 2015;Chug et al, 2015). In addition, it is now well established that distinct structures (e.g.…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%